PENGARUH CORPORATE SOCIAL RESPONSIBILITY, CAPITAL INTENSITY DAN INTENSITAS PERSAINGAN TERHADAP AGRESIVITAS PAJAK - Wulandari, Trian; Wulandari, Evita Vibriana (Publika Citra Media, 2024)
This research aims to provide empirical evidence of the influence of Corporate Social Responsibility, Capital Intensity, and Competition Intensity on Tax Aggressiveness for manufacturing companies listed on the BEI in 2018-2022. This research applies quantitative research methodology with secondary data as the data type. Purposive sampling was applied by researchers to be able to select samples for this study. The total data obtained was 40 data. The data analysis technique uses multiple linear regression analysis. Data processing using e-views 12. The results of this research show that Corporate Social Responsibility, Capital Intensity, and Competition Intensity simultaneously influence Tax Aggressiveness. The partial research results show that Capital Intensity and Competition Intensity have an effect on Tax Aggressiveness, while partial Corporate Social Responsibility has no effect on Tax Aggressiveness.